Pelatihan Industri Kreatif bagi Ibu-ibu Pembinaan Kesejahteraan Keluarga (PKK) di Kelurahan Jayengan Kota Surakarta - Mubarok, Novan; Estiwati, Uliya; Nugraha, Didik (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The technical movement in supporting the family economy is the goal of the movement for the formation of Family Welfare Development (PKK). To support the family economy, a housewife as a special target for PKK, must have the ability or creativity, especially in the field of creative industry-based entrepreneurship. This activity aims to: 1) develop creative industry skills in making/producing woven sticks, and 2) increasing the ability to use information technology as a marketing medium for woven sticks produced by PKK women in Jayengan Village, Surakarta City. This service is carried out by providing short training for one day which was attended by 23 participants from 35 targeted participants. Based on the results of observations of community service activities, PKK women in Jayengan Village were very enthusiastic in carrying out the training. This can be seen from the number of participants who actively ask questions and show high attention. The results of this community service activity are PKK women have an entrepreneurial spirit, have the ability to use information technology as a marketing tool, and can make woven stick plates with various designs that are suitable for sale.